Efficacy and safety of Tofacitinib in patients with active rheumatoid arthritis resistant to conventional therapy: Preliminary results of an open-label clinical trial - E. L. Luchikhina; D. E. Karateev; N. V. Demidova; A. S. Musiyuk; E. N. Aleksandrova; A. A. Novikov; A. V. Smirnov; E. L. Nasonov (Современная ревматология, 2016)
Despite the advances in the therapy of rheumatoid arthritis (RA), which are associated with the use of biological anti-rheumatic drugs, the problemof effective treatment of RA is not still solved. Inclusion of new methods in treatment strategies, in particular the so-called «small molecules», i.e. synthetic compounds acting on intracellular signaling pathways, such as Tofacitinib (TOFA) approved for use in rheumatologic practice, is very important.Objective: to evaluate the efficacy and safety of therapy with TOFA in combination with synthetic disease-modifying anti-rheumatic drugs (s-DMARDs), primarily methotrexate (MTX) in in patients with active RA in real clinical practice.Subjects and methods. This ongoing open-label trial is a part of the scientific program «Russian Investigation of Methotrexate and Biologics in Early Active Inflammatory Arthritis» (REMARCA) that explores the possibility of adapting the «treat-to-target» strategy in real prac-tice in Russia. The study included RA patients with moderate to high disease activity despite treatment with MTX or other DMARDs. A total of 41 patients with RA were included (8 males, 33 females; mean age 52.6±14.2 years, disease duration 47.2±49.7 months, 82.9% RF+ and 80.5% anti-CCP+,DAS28-ESR 5.45±0.95, SDAI 30.2±12.2). All the patients had previously received s-DMARDs; 12 (29.3%) patients also had biological DMARDs (1 to 4 biologics). Oral TOFA 5 mg in combination with MTX or leflunomide was administered twice daily to 40 and 1 patients, respectively, with the possibility of increasing the dose up to 10 mg BID. To date, 37 and 12 patients received TOFA for 3 and 6 months, respectively.Results. TOFA was used as a second-line drug (after s-DMARDs failure) in 29 (70.7%), as a third line drug (after s-DMARDs and biologics failure) in 12 (29.3%) patients. The dose was escalated to 10 mg BID in 13 (31.2%) patients, on the average, 11.2±1.7 weeks after treatment initiation. TOFA was not discontinued in the reporting period. There was a significant reduction in disease activity following just 4 weeks of TOFA therapy. At 3 months, 27% of patients achieved low disease activity (LDA) by the SDAI; 29.7% had SDAI remission; 35% had HAQ ≤0.5; at 6 months, LDA, SDAI remission, had HAQ ≤0.5 were seen in 41.7, 41.7, and 67%, respectively. There were no significant differences in the suppression of RA activity depending on whether second- or third-line TOFA therapy was performed. There were no serious adverse events (SAEs) or serious infections.Conclusions. Second- and third-line TOFA therapy allows the majority of patients to quickly achieve the T2T goals (56.7 and 83.4% of patients at 3 and 6 months, respectively), so the drug can be quite successfully «integrated» into the T2T strategy along with biologics. The drug effectively inhibits granulomatous inflammation (by the example of rheumatoid nodules) and shows a sufficient safety (no SAEs).